Orbital-symmetry-dependent electron transfer through molecules assembled on metal substrates - Blobner, Florian; Zharnikov, Michael (The journal of physical chemistry letters, 2012)
Femtosecond charge-transfer dynamics in self-assembled monolayers of cyano-terminated ethane-thiolate on gold substrates was investigated with the core hole clock method. By exploiting symmetry selection rules rather than energetic selection, electrons from the nitrogen K-shell are state-selectively excited into the two symmetry-split π* orbitals of the cyano end group with X-ray photons of well-defined polarization. The charge-transfer times from these temporarily occupied orbitals to the metal substrate differ significantly. Theoretical calculations show that these two π* orbitals extend differently onto the alkane backbone and the anchoring sulfur atom, thus causing the observed dependence of the electron-transfer dynamics on the symmetry of the orbital.